Pregnancy-Induced Hypertension: A Descriptive Study Concerning Nurses’ Knowledge at Lady Wallington, Lahore, Pakistan - Nazar, Tayyba; Khalid, Rabia; Fatima, Aliza (Journal of Development and Social Sciences, 2024)
The objective of study is to assess nurses’ knowledge concerning pregnancy-induced hypertension at Lady Wallington Hospital. Pregnancy-induced hypertension (PIH) is the most common pregnancy complication, the most common cause of maternal death, and a contributing factor to neonatal morbidity and mortality. A descriptive study was conducted in Lady Wallington Hospital, Lahore. There were one hundred nurses in a non-probability purposive sample. Nurses completed self-report, structured questionnaires in the Gynecology Ward including the emergency room and wards medical (using a purposive and non-probability sample). The results show that the bulk of the sample (80%) was between the ages of 31 and 39. The table also reveals that women make up the majority of study participants (56%) and that over half of them were single (56%). About 52% of the study sample had a college nursing degree, and 50% of the sample's total service years were between 11 and 20 years old. The examination of nurses' knowledge about gestational hypertension revealed a good degree of understanding. The study concluded that the knowledge of a good level of nurses about pregnancy-induced hypertension. It is recommended that on-the-job refresher courses are needed.